Features of spatial variability of a hydrogen sulfide field in the Black Sea off the Northern Caucasus. - Neretin, Lev N; Demidova, Tatyana P; Volkov, Igor I (PANGAEA, 1997)
Features of spatial variability of hydrogen sulfide in the northeastern part of the Black Sea are estimated. Some technical aspects of H2S concentration determination in the anoxic zone are discussed: in its upper part at H2S concentration <30 µmol/l, the photometric method is recommended, while for deeper layers the iodometric method should be used. With linearity of vertical distribution of hydrogen sulfide and ammonium taken into account their vertical gradients are estimated as 0.49+/-0.04 µmol/m and 0.19+/-0.06 µmol/m respectively. It is shown that the upper boundary of the H2S layer corresponds to the isopycnal surface with Sigma_t = 16.19+/-0.05 arbitrary units. Special attention is paid to relationship of hydrogen sulfide distribution with hydrophysical features in the region under study, in particular in the coastal zone. It is shown that hydrodynamic conditions control spatial distribution of hydrogen sulfide. On the basis of isopycnal treatment of the H2S field existence of a coastal convergence zone is proved, and peculiarities are recognized of vertical circulation in the main Black Sea gyre and coastal anticyclonic eddies; here hydrogen sulfide serves as a tracer of hydrophysical mixing processes.
Some hydrophysical and hydrochemical parameters of the upper part of the hydrogen sulfide zone in the Black Sea, September 11-22, 1994
Keywords: Akvan94-1003; Akvan94-1004; Akvan94-1005; Akvan94-1006; Akvan94-1007; Akvan94-1008; Akvan94-1016; Akvan94-1018; Akvan94-1019; Akvan94-1020; Akvan94-1021; Akvan94-1022; Akvan94-1023; Akvan94-1024; Akvan94-1025; Akvan94-1026; Akvan94-1027; Akvan94-1028; Akvan94-1029; Akvan94-1031; Akvan94-1032; Akvan94-1034; Akvan94-1035; Akvan94-1036; Akvan94-1037; Akvan94-1038; Akvan94-1039; Akvan94-1040; Akvan94-1041; Akvan94-1042; Akvan94-1043; Akvan94-1044; Akvan94-1044_1; Akvan94-1044_10; Akvan94-1044_7; Akvan94-1045; Akvan94-1046; Akvan94-1054; Akvan94-1055; Akvan94-1056; Akvan94-1057; Akvan94-1058; Akvan94-1059; Archive of Ocean Data; ARCOD; Black Sea; MULT; Photometry; Position in the field of Sigma t; Titration; Vertical gradient; Vertical gradient of ammonium concentration; Vertical gradient of hydrogen sulfide concentration; Zone boundary, upper